2010
DOI: 10.1136/ard.2010.129148
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 is not a crucial regulator in an animal model of tumour necrosis factor-mediated bilateral sacroiliitis

Abstract: IL-6 is not a crucial regulator in an animal model of TNF-mediated bilateral, erosive sacroiliitis. This finding questions the potential of IL-6 blockade as a new treatment in patients with AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…MMP3, a stromelysin, and MMP13, a collagenase, key enzymes in extracellular matrix remodelling, which have both been shown to be elevated in AS as well as animal models [34,44,45], were both strongly upregulated. The strong matrix formation response was also reflected with marked upregulation of the key bone matrix components Col1, bone sialoprotein and OCN, as well as a number of other extracellular matrix-associated genes.…”
Section: Discussionmentioning
confidence: 99%
“…MMP3, a stromelysin, and MMP13, a collagenase, key enzymes in extracellular matrix remodelling, which have both been shown to be elevated in AS as well as animal models [34,44,45], were both strongly upregulated. The strong matrix formation response was also reflected with marked upregulation of the key bone matrix components Col1, bone sialoprotein and OCN, as well as a number of other extracellular matrix-associated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Mice over-expressing human TNF (hTNF.Tg mice), which are characterised by focal bone erosion similar to RA, and bilateral sacroilitis associated with new bone for-mation similar to ankylosing spondylitis, have been shown to have high serum IL-6 levels (94). Genetic deletion of IL-6 expression in this model, did not modify the development of inflammation and bone formation associated with the bilateral sacroilitis, suggesting that IL-6 may not mediate these features of ankylosing spondylitis (94). However, the potential for gp130 cytokines such as OSM to downregulate the expression of Wnt signalling antagonists such as sclerostin in osteocytes (43), leaves open the possibility for gp130 cytokines to mediate the enhanced bone formation in the form of syndesmophytes in the spondylarthropathies and should be further investigated in models not dependent on TNF over-expression.…”
Section: Spondylarthropathies (Eg Ankylosing Spondylitis Psoriaticmentioning
confidence: 99%
“…Visvanathan et al [12] showed a correlation between the baseline IL-6 level and the MRI score and BASDAI. On the other hand, a role for IL-6 in the pathogenesis of AS was not considered crucial in a study using IL-6 knockout TNF-a transgenic mice that developed sacroiliitis [13]. Also, the correlation between AS severity and IL-6 level was not always consistent [14].…”
Section: Discussionmentioning
confidence: 97%